2021
DOI: 10.1002/humu.24205
|View full text |Cite
|
Sign up to set email alerts
|

CNGB1 ‐related rod‐cone dystrophy: A mutation review and update

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 103 publications
2
21
2
Order By: Relevance
“…Abnormal hyperAF ring phenotypes on FAF have been reported in 59–68% of RP patients, depending on genetic cause [ 31 , 32 ]. A recent review identified ring phenotypes on quantitative FAF in 79.3% of RP patients with CNGB1 mutations, similar to our cohort of 69.7% [ 11 ]. These differing FAF phenotypes did not appear correlated with age or genotype in this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Abnormal hyperAF ring phenotypes on FAF have been reported in 59–68% of RP patients, depending on genetic cause [ 31 , 32 ]. A recent review identified ring phenotypes on quantitative FAF in 79.3% of RP patients with CNGB1 mutations, similar to our cohort of 69.7% [ 11 ]. These differing FAF phenotypes did not appear correlated with age or genotype in this study.…”
Section: Discussionsupporting
confidence: 88%
“…There was no clear inflection point to determine if the rate changed with age. ERM prevalence in our study is higher than in previously reported CNGB1 cohorts (34.8% in Nassisi et al and 20% in Hull et al), but has been reported in up to 64% from other RP cohorts, precluding the use of central retinal thickness as a reliable outcome measure [ 10 , 11 , 30 ]. Abnormal hyperAF ring phenotypes on FAF have been reported in 59–68% of RP patients, depending on genetic cause [ 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations